A 22‐37 GHz low noise amplifier with 2.8 dB mean noise figure and +22.9 dBm output 3rd‐order intercept point for 5th generation applications. Issue 9 (13th March 2019) - Ma, Qian; Xiang, Yuanjiang
Abstract: This paper presents a wideband 22‐37 GHz low noise amplifier (LNA) realized in a 0.25 μm SiGe BiCMOS technology. The design incorporates additional noise matching between the cascode transistors to minimize the noise figure (NF) degradation. The second stage incorporates an active balun architecture with a tail inductor to improve the common‐mode rejection ratio (CMRR). To extend the bandwidth, a capacitive feed forward path is added at the second stage. The LNA presents a minimum in‐band NF of 2.3 dB from 22‐37 GHz. The achieved 3 dB‐gain bandwidth is larger than 15 GHz, with a peak gain of 20.8 dB at 28 GHz. The output 3rd‐order intercept point (OIP3) is +22.9 dBm for a total power consumption of 94 mW. The area of the core circuit is 0.35 × 0.47 mm 2 . To the author's knowledge, the LNA shows the best overall performance compared to the existing silicon‐based LNAs.